The mummy (USA: Universal Studios [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor], 2000)
Deep in Egyptian desert, a handful of people serching for a long-lost treasure have just unearthed a 3,000 year old legacy of terror
Executive producer, Kevin Jarre
Cast: Brendan Fraser
Keywords: Horror films; Ghosts in motion pictures